Radiofrequency Ablation for Early-Stage Nonsmall Cell Lung Cancer. (3rd June 2014) - Hiraki, Takao; Gobara, Hideo; Iguchi, Toshihiro; Fujiwara, Hiroyasu; Matsui, Yusuke; Kanazawa, Susumu
Abstract : This review examines studies of radiofrequency ablation (RFA) of nonsmall cell lung cancer (NSCLC) and discusses the role of RFA in treatment of early-stage NSCLC. RFA is usually performed under local anesthesia with computed tomography guidance. RFA-associated mortality, while being rare, can result from pulmonary events. RFA causes pneumothorax in up to 63% of cases, although pneumothorax requiring chest drainage occurs in less than 15% of procedures. Other severe complications are rare. After RFA of stage I NSCLC, 31–42% of patients show local progression. The 1-, 2-, 3-, and 5-year overall survival rates after RFA of stage I NSCLC were 78% to 100%, 53% to 86%, 36% to 88%, and 25% to 61%, respectively. The median survival time ranged from 29 to 67 months. The 1-, 2-, and 3-year cancer-specific survival rates after RFA of stage I NSCLC were 89% to 100%, 92% to 93%, and 59% to 88%, respectively. RFA has a higher local failure rate than sublobar resection and stereotactic body radiation therapy (SBRT). Therefore, RFA may currently be reserved for early-stage NSCLC patients who are unfit for sublobar resection or SBRT. Various technologies are being developed to improve clinical outcomes of RFA for early-stage NSCLC.